ANALISIS KAPASITAS SIMPANG TAK BERSINYAL PADA SIMPANG TIGA - B. Erdiansyah Putra (Program Studi Teknik Sipil, Fakultas Teknik Universitas Teknologi Sumbawa, 2025)
Unsignalized intersections are a major point of concern due to the increasing number of vehicles. Bima City is a city located on the eastern part of Sumbawa Island, West Nusa Tenggara Province. As a developing city, congestion and busy traffic often occur on roads or intersections of Mongosidi and Anggrek roads. Therefore, this study was conducted to determine the performance and level of service of unsignalized intersections at Mongosidi Street and Anggrek Street. The method used refers to the Indonesian Road Capacity Manual (MKJI) 1997. This study aims to determine the indicators of traffic behavior at unsignalized intersections. The results of the calculation obtained a total flow of 3147 smp / hour, a capacity value (C) of 4234 smp / hour and a degree of saturation (DS) of 0.74, Traffic Delay (DT) of 8.07 sec / smp, intersection delay (D) of 11.73 sec / smp and upper and lower limit queuing opportunities of 44.46% and 17.74% respectively. This condition occurs on Monday, March 17, 2025 at the peak hour of 06.45-07.45 WITA. For the level of service of the intersection pattern, the conditions on Monday, March 17, 2025 at the peak hour of 06.45-07.45 WITA are also categorized as type C, namely stable flow, but the speed and movement of vehicles are controlled.Drivers are limited in choosing speed, with saturation density (Ds) around 0.45 - 0.74.